2022
DOI: 10.1007/s00217-022-03974-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wet extrudates from pumpkin seed proteins on drying, texture, and appearance of dry-cured hybrid sausages

Abstract: Hybrid meat products represent a promising, more sustainable alternative to all-meat formulations. However, differences among plant- and animal-based proteins may alter traditional handling and final product properties. In this study, pork meat was partially replaced with texturized pumpkin seed proteins at 12.5, 25, 37.5, and 50% to obtain dry-cured hybrid meat sausages and their ripening (acidification, drying) during 21 days and final product properties (texture, sensory) were characterized and compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
2
2
0
2
Order By: Relevance
“…During the fermentation stage, no significant difference (p > O.05) was observed between these three batches, indicating that the addition of cloves did not impact the raw values. These results are in agreement with previous work by Ebert et al (2022) who found values of 0.909 ± 0.006 and 0.898 ± 0.004 respectively on days 1 and 21 of the fermentation. Our results disagree with those of Fernández-Diez et al (2016) who observed a decrease in the level of raw sausages enriched with boiled quinoa during drying attaining values of 0.83 and 0.85 for control and half-fat sausages, respectively.…”
Section: Evolution Of Physico-chemical Parameters Of Sausages During ...supporting
confidence: 94%
See 1 more Smart Citation
“…During the fermentation stage, no significant difference (p > O.05) was observed between these three batches, indicating that the addition of cloves did not impact the raw values. These results are in agreement with previous work by Ebert et al (2022) who found values of 0.909 ± 0.006 and 0.898 ± 0.004 respectively on days 1 and 21 of the fermentation. Our results disagree with those of Fernández-Diez et al (2016) who observed a decrease in the level of raw sausages enriched with boiled quinoa during drying attaining values of 0.83 and 0.85 for control and half-fat sausages, respectively.…”
Section: Evolution Of Physico-chemical Parameters Of Sausages During ...supporting
confidence: 94%
“…The S2 batch showed the lowest moisture content on day 15 attaining values of 21.36% versus 26.52 and 25.30 for S1 and Control batches, respectively. Our results are in agreement with the trend observed by Ebert et al (2022) who observed a decrease in the moisture content in the control sausages and the hybrid sausages containing textured pumpkin seeds at 50% from 61.2 ± 0.7% to 55.1 ± 0.1% on day 1 and 21 of fermentation time. This could also explain the slightly lower aw of S1 and S2 batches.…”
Section: Evolution Of Physico-chemical Parameters Of Sausages During ...supporting
confidence: 93%
“…The increase in weight loss usually follows the rate of increase in free water. A food product is said to be stable if it has a low weight loss value [38].…”
Section: Weight Lossmentioning
confidence: 99%
“…Furthermore, using plant-instead of animal-based proteins may also cause process-related changes due to variations in their techno-functionality. For example, Ebert et al (29) have recently shown that using texturised pumpkin seed proteins alters the drying behaviour of dry-cured meat hybrids, thereby 10.3389/fnut.2023.1101479 causing alterations in texture and free water. Finally, nutritional quality needs to be considered, as the bioavailability of meat and plant proteins differ.…”
Section: Consumers' Sensory Evaluation Of Meat Blendsmentioning
confidence: 99%